2013 IEEE International Conference on Technologies for Homeland Security (HST) 2013
DOI: 10.1109/ths.2013.6699079
|View full text |Cite
|
Sign up to set email alerts
|

Application of pyramidal directional filters for biometric identification using conjunctival vasculature patterns

Abstract: Directional pyramidal filter banks as feature extractors for ocular vascular biometrics are proposed. Apart from the red, green, and blue (RGB) format, we analyze the significance of using HSV, YCbCr, and layer combinations (R+Cr)/2, (G+Cr)/2, (B+Cr)/2. For classification, Linear Discriminant Analysis (LDA) is used. We outline the advantages of a Contourlet transform implementation for eye vein biometrics, based on vascular patterns seen on the white of the eye. The performance of the proposed algorithm is eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Since its introduction by Derakhshani and Ross, other researches have been introducing various segmentation, image enhancement, feature extraction, and classification algorithms for conjunctival vasculature biometrics. So far, eyeprint biometric studies have been performed either by utilising UBIRIS v1 RGB dataset, or researchers' in-house ocular images [12,13,[16][17][18][19][20][21][22][23][24][25][26][27][28][29]. Some studies have also reported using multispectral captures [30,31].…”
Section: Iet Biometricsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since its introduction by Derakhshani and Ross, other researches have been introducing various segmentation, image enhancement, feature extraction, and classification algorithms for conjunctival vasculature biometrics. So far, eyeprint biometric studies have been performed either by utilising UBIRIS v1 RGB dataset, or researchers' in-house ocular images [12,13,[16][17][18][19][20][21][22][23][24][25][26][27][28][29]. Some studies have also reported using multispectral captures [30,31].…”
Section: Iet Biometricsmentioning
confidence: 99%
“…The initial enhancement and registration schemes were reported in [17] using a 50 subject in-house database. The performance of gray-level cooccurence matrix (GLCM) [18] and pyramidal directional filter [19] features were investigated using dSLR captures. In related work [21][22][23][24][25][26][27][28][29], several methods were evaluated on UBIRISv1 database [20] compared with in-house datasets.…”
Section: Related Workmentioning
confidence: 99%
“…Crihalmeanu et al [20] used multispectral imaging in combination with Speeded Up Robust Features (SURF), pixel-topixel correlation, and minutiae points for feature extraction. In our previous work, we used wavelet packet energies [21], contourlets [10], shearlets [22], and the grey level co-occurrence method (GLCM) [11] for OSV feature extraction. Oh et al [23] used local binary pattern features for OSV recognition.…”
Section: Reported Osv Feature Extraction Schemesmentioning
confidence: 99%
“…In [10], CIBIT‐II dataset was used for OSV recognition using contourlets, with a best EER of 0.04% being reported for short‐term analysis. In this study, using curvelets, an EER of 0.01% was obtained for the same scenario.…”
Section: Comparative Analysismentioning
confidence: 99%
See 1 more Smart Citation